How Do Oil Prices Affect the GDP and Its Components? New Evidence from a Time-Varying Threshold Model - Leila Ben Salem; Ridha Nouira; Sami Saafi; Christophe Rault (Institute of Labor Economics (IZA), 2024)
Revealing the precise thresholds at which fluctuations in oil prices start to affect gross domestic product and its various components (consumption, investment, expenditure and exports) holds significant implications for policymakers in both oil-importing and oil-exporting countries. Existing studies assessing the effects of oil prices on economic activity typically assume constant or stable threshold values. However, recent evidence suggests that this restrictive assumption may not accurately capture the dynamic nature of these relationships. We address this issue by adopting a more realistic framework that allows for the possibility that oil prices will have a time-varying effect on economic activity. We also employ the innovative time-varying threshold regression kink model of Yang and Su (2018). Our analysis focuses on a sample of 20 top oil-importing and oil-exporting countries during the period 1995Q1 to 2023Q2. The findings of our investigation provide compelling evidence to support the existence of time-varying threshold levels in the relationship between oil prices and macroeconomic activity for most countries in our sample. Notably, our research unveils a substantial heterogeneity in the oil price thresholds across the investigated countries, thereby challenging the notion of a universal threshold applicable to all.
Keywords: C5; Q4; Q43; 330; oil-importing countries; time-varying threshold; GDP and its components; oil price; oil-exporting countries